Animal behaviour and algal camouflage jointly structure predation and selection. (22nd March 2018) - Start, Denon
Abstract: Trait variation can structure interactions between individuals, thus shaping selection. Although antipredator strategies are an important component of many aquatic systems, how multiple antipredator traits interact to influence consumption and selection remains contentious. Here, I use a common larval dragonfly ( Epitheca canis ) and its predator ( Anax junius ) to test for the joint effects of activity rate and algal camouflage on predation and survival selection. I found that active and poorly camouflaged Epitheca were more likely to be consumed, and thus, survival selection favoured inactive and well‐camouflaged individuals. Notably, camouflage dampened selection on activity rate, likely by reducing attack rates when Epitheca encountered a predator. Correlational selection is therefore conferred by the ecological interaction of traits, rather than by opposing selection acting on linked traits. I suggest that antipredator traits with different adaptive functions can jointly structure patterns of consumption and selection.